EFFECT OF AIR COOLING AND VACUUM COOLING STORAGE ON PROXIMATE CONTENT (WATER, pH, PROTEIN AND SUGAR) AND β-CAROTENE OF KABOCHA YELLOW PUMPKIN (Cucurbita maxima L.) - Triana Kusumaningsih; Tri Martini; Lestari Okstafiyanti; Kartika Setia Rini (Alchemy)
ABSTRACT